عندما تصنع الوثیقةُ الھویّ ةتجربة الأرم نبین القیود القانونیة وتشكّل الذات الیومی ة - فاطمة صلا ح (տպ. Atlas)
The author notes that a significant number of Armenians living in Egypt had no legal documents that identified them. Some of these Armenians were born in Egypt and had lived there for over half a century. However, due to lack of any sort of documentation they faced the problem of identifying themselves as Egyptians, Armenians, refugees, etc. when they applied for citizenship. Based on state archival documents in the Shubra region of Egypt, the article focuses on such conflicts between the identity of the self, which is based on the daily life of the individual , and the one which is based on legal documents , in other words, the conflict between the self -perception of the individual and that of the state.
Keywords: History; Egypt; Armenian diaspora